2014
DOI: 10.1021/ac404050t
|View full text |Cite
|
Sign up to set email alerts
|

High Temporal Resolution Measurements of Dopamine with Carbon Nanotube Yarn Microelectrodes

Abstract: Fast-scan cyclic voltammetry (FSCV) can detect small changes in dopamine concentration; however, measurements are typically limited to scan repetition frequencies of 10 Hz. Dopamine oxidation at carbon-fiber microelectrodes (CFMEs) is dependent on dopamine adsorption, and increasing the frequency of FSCV scan repetitions decreases the oxidation current, because the time for adsorption is decreased. Using a commercially available carbon nanotube yarn, we characterized carbon nanotube yarn microelectrodes (CNTYM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
146
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 101 publications
(150 citation statements)
references
References 62 publications
4
146
0
Order By: Relevance
“…Researchers have found that ferric hydroxide-Nafion film-coated carboxylic acid-modified carbon nanotubes changed dopamine in drosophila [40]. Functionalization of carbon nanotubes with poly (diallyl dimethylammonium chloride) (PDDA) reduced the detection limit of dopamine [41] .…”
Section: Advances In the Therapeutic Effects Of Carbon Nanotubes On Mmentioning
confidence: 99%
“…Researchers have found that ferric hydroxide-Nafion film-coated carboxylic acid-modified carbon nanotubes changed dopamine in drosophila [40]. Functionalization of carbon nanotubes with poly (diallyl dimethylammonium chloride) (PDDA) reduced the detection limit of dopamine [41] .…”
Section: Advances In the Therapeutic Effects Of Carbon Nanotubes On Mmentioning
confidence: 99%
“…CNT yarns are made of multiple CNT fibres twisted together and these have been utilized by Yang and team for production of CNT yarn microelectrodes (CNTYMEs). The CNTYMEs are used for speedy measurements of dopamine [85]. CNTs can be used to determine the level of disease severity and other pathological conditions.…”
Section: Carbon Nanotubes As Electrochemical Biosensors In Neurosciencementioning
confidence: 99%
“…Our group utilized a commercially-available CNT yarn fabricated microelectrodes for dopamine detection with LOD of 13 ± 2 nM. 93 We also found the dopamine signal is independent to the repetition rate with FSCV at CNT yarn microelectrodes, an advantage over conventionally used CFMEs which lose sensitivity with increasing repetition rate ( Fig. 1.2).…”
Section: Carbon Nanotube-fiber Microelectrodesmentioning
confidence: 83%
“…138,139 Our group has recently discovered that at CNTYMEs, the dopamine current does not change significantly with increasing scan repetition frequency: at a scan rate of 2000 V/s, dopamine can be detected, without any loss in sensitivity, with scan frequencies up to 500 Hz. 93 Thus, the temporal resolution is four times faster without a decrease in signal. The cause of this increased temporal resolution is differences in dopamine and DOQ adsorption and desorption kinetics; at CNTYMEs, the rates of desorption for dopamine and DOQ are almost identical, while at CFMEs, the rate of desorption for DOQ is over an order of magnitude higher than that for dopamine.…”
Section: Yang| 26mentioning
confidence: 97%
See 1 more Smart Citation